2008
DOI: 10.1159/000112957
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emollients in the Management of Diseases with Chronic Dry Skin

Abstract: Dry skin is a common skin condition as well as a key aspect of a number of diseases such as atopic dermatitis and psoriasis but also of other diseases and systemic conditions. Dry skin has an impact on the patient in terms of discomfort, pruritus and impaired quality of life. Within the overall treatment regimen for these diseases, the use of emollients to manage dry skin plays a considerable role in managing skin conditions. In atopic dermatitis and psoriasis, emollients help to improve skin condition and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 66 publications
1
51
0
7
Order By: Relevance
“…Deficient skin barrier function leading to increased transepidermal water loss (TEWL) and decreased stratum corneum hydration (dry skin) is a characteristic feature of AD (22,23). Clinical studies showed that the daily use of skin care products may prevent AD or can prolong the time between flare-ups (24)(25)(26).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Deficient skin barrier function leading to increased transepidermal water loss (TEWL) and decreased stratum corneum hydration (dry skin) is a characteristic feature of AD (22,23). Clinical studies showed that the daily use of skin care products may prevent AD or can prolong the time between flare-ups (24)(25)(26).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…18 Topical moisturizers are beneficial for managing dry skin, 19 with many studies showing demonstrable improvements in skin condition compared to use of a moisturizer with placebo base cream, although no conclusive recommendations were reached in a systematic review. 20 Although no particular ingredient or formulation of moisturizer could be recommended, this study revealed that application of moisturizer for prevention of fissure in patients with diabetes should be followed for a suggested skin hydration of 20.0%.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…American Diabetes Association -ADA) stosowanie emolientów jest wskazane u diabetyków w profilaktyce suchej skóry i świądu [40]. Emolienty to preparaty miejscowo nawilżające i natłuszczające skórę.…”
Section: Pielęgnacja Skóry Cukrzycowejunclassified